Libertà morale e accertamenti neuroscientifici: profili costituzionali (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Relationship between the neuroscientific assessments used during the penal trial and the moral freedom of the subject; drawing of demarcation lines for the “concept” of moral freedom according to the guidelines of the doctrine; a statement indicating whether or not moral freedom is constitutionally protected; in-depth examination of the implications between Article 188 Code of Criminal Procedure and Article 13 of the Constitution; verifying whether or not the neuroscientific techniques should be admitted in the penal trial and to what extent; in-depth examination of the relationship between the principle of human dignity “Nemo tenetur se detegere” and moral freedom.
Keywords: Neuroscientific assessments; moral freedom; Constitution; penal trial; Article 188 of the Code of Criminal Procedure